2007
DOI: 10.2215/cjn.01880606
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Use of Arteriovenous Fistula in Hemodialysis

Abstract: The Fistula First Initiative set a goal of 66% arteriovenous (AV) fistula-based access among US hemodialysis patients. This study modeled the impact of achieving the target AV fistula placement rate on Medicare expenditures and on dialysis patient survival and also reviewed economic disincentives for providers that will inhibit achieving this target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 21 publications
(14 reference statements)
0
44
0
2
Order By: Relevance
“…Several authors have identified changes in the process of care to improve the rate of AVF use among incident patients (22,26,27), and one author suggests financial incentive based on the cost-effectiveness of the AVF (28). Understanding patient preference, beliefs, values, and reasons for refusal will be necessary to appropriately address this significant proportion of eligible patients who simply refuse a permanent access.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have identified changes in the process of care to improve the rate of AVF use among incident patients (22,26,27), and one author suggests financial incentive based on the cost-effectiveness of the AVF (28). Understanding patient preference, beliefs, values, and reasons for refusal will be necessary to appropriately address this significant proportion of eligible patients who simply refuse a permanent access.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Because AVF requires fewer angiographic procedures and revisions, use of an AVF can also reduce the cost of vascular access-related care up to fivefold, 8,9 and multiple sources suggest that use of an AVF is cost-effective when compared with other vascular accesses. 10,11 Ideally, the AVF is placed and ready to use at the initiation of HD, but this process is highly dependent on predialysis nephrology care. 12,13 In the United States, this complex process generally requires early nephrology referral, selection of HD as preferred dialysis modality, estimation of time to HD, surgical referral, vascular imaging, preoperative evaluation, operative procedure, frequent follow-up visits to assess AVF maturation, and sometimes repeat surgical procedures.…”
mentioning
confidence: 99%
“…Therefore, given the increasing number of patients on HD in Brazil, 20 it is important to implement a care program to ESRD patients that includes establishing an adequate arteriovenous access prior to HD, which in turn may be cost-effective and ultimately improve these patients' quality of life. 18,23 Further investigations are needed to explore the characteristics of dialysis services that may influence establishing a permanent vascular access for HD.…”
Section: Discussionmentioning
confidence: 99%